Workers and alate queens of Solenopsis geminata share qualitatively similar but quantitatively different venom alkaloid chemistry - Shi, Qun-Hui; Hu, Lin; Wang, Wen-Kai; Vander Meer, Robert K.; Porter, Sanford D.; Chen, Li (Frontiers in Ecology and Evolution, 2015)
Solenopsis geminata group (Hymenoptera: Formicidae) encompasses ant species commonly called fire ants because of their painful sting. The many physiological effects of the venom are caused by 2-methyl-6-alkyl and/or alkenylpiperidine alkaloids. The variation in piperidine alkaloid structures has useful taxonomic characters. The most well studied Solenopsis species is S. invicta, which was accidentally imported into the USA in the 1930s from South America. It quickly spread throughout the southern USA and is now a major invasive pest ant in the USA and in other parts of the world. Interestingly, the invasive S. invicta has largely displaced a native USA fire ant, S. geminata, from the southern USA. We explore the possibility that differences in venom chemistry could be correlated with this displacement. The cis and trans alkaloids from body extracts of workers and alate queens of S. geminata were separated by silica gel chromatography, identified, and quantitated by GC-MS analysis. Both workers and alate queens produce primarily cis- and trans-2-methyl-6-n-undecyl-piperidines, as well as other minor alkaloid components. Imported fire ant, S. invicta, alate queens produce the same alkaloids as S. geminata alate queens, but in contrast S. invicta workers produce piperidine alkaloids with longer side chains, which are purported to be physiologically more effective. These results are discussed in relation to the evolutionary progression of fire ant venom alkaloids and displacement of S. geminata by S. invicta in the USA.